Effects of sulfonation process on thermal behavior and microstructure of sulfonated polysulfone membranes as a material for Proton Exchange Membrane (PEM) - Naim, R.; Ismail, A. F.; Saidi, H. (2004)
This paper reports the effect of sulfonation processon thermal behavior and microstrucutre of sulfonated polysulfone membrane. Various degree of sulfonation reactin has been conducted and the sulfonated membranes were characterized by thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), x-ray diffraction (XRD) and scanning electron microscopy (SEM). Modifications of the origin polysulfone polymer resulted in an increment value of glass transition temperature (Tg) due to the introduction of sulfonic acid group to the polymer backbone. However, due to some hindrance such as trace amount of organic solvent left during solvent evaporation and high hydrophilicity of the produced sulfonated membranes resulted in decreasing values of Tg. The polymer membrane showed lower degradation temperature as a function of degree of sulfonation. From XRD analysis, it was found that the membrane shows slight crystalline behavior after the sulfonation reaction. Detail discussions and observation of the alteration in microstructure of the sulfonated membrane were supported by SEM micrograph.